Type 1 Diabetes (T1D) and Latent Autoimmune Diabetes in Adults (LADA): The Difference Between a Honeymoon and a Holiday - Livia M. R. Marcon; Carmine G. Fanelli; Riccardo Calafiore (Case Reports in Endocrinology)
Type 1 diabetes mellitus (T1D) is a chronic autoimmune disease in which destruction of the insulin-producing β-cells in the pancreatic islets requires regular lifelong insulin replacement therapy, the only lifesaving treatment available at this time. In young persons with a genetic predisposition, it usually manifests after being exposed to environmental triggers. A subtype of autoimmune diabetes mellitus (ADM) that typically occurs in adulthood is often referred to as latent autoimmune diabetes of adults (LADA). LADA is characterized by a milder process of β-cells destruction and less intensive insulin treatment, which may become necessary even many years after diagnosis. Genetic predisposition of T1D carries an increased risk for other autoimmune diseases, such as autoimmune thyroiditis, the most frequently associated condition, and pernicious anaemia (PA), present in approximately 4% of all individuals with T1D. Here, we describe the case of a 90-year-old woman with vitiligo and a mute medical history who was admitted to our University Hospital in Perugia with hyperglycaemia and severe anaemia due to vitamin B12 (VB12) depletion. A short time after setting the beginning treatment with a basal-bolus insulin regimen, her insulin requirement rapidly declined and treatment with sitagliptin, a dipeptidyl peptidase-4 inhibitor (DPP4), was started. A complete autoimmunity screening panel showed that GAD65 and intrinsic factor autoantibodies were positive.